Chronically ill Patients, Life Incidents and Reactive Strategies: A Qualitative Study among Patients Suffering from four Types of Diseases, Followed-up in the North-Eastern of Italy - Natascia Bobbo; Chiara Bottaro; Estella Musacchio (University of Bologna, 2022)
Living with a chronic condition represents a strenuous experience that often could be lived as a sequence of waiting and crisis times. Therapeutic path incidents could represent however a catalysts and revelatory time, useful to patients to discover their own resources. A qualitative study according to the phenomenological hermeneutic perspective was conducted to understand the kind of skills expressed by the patients during a difficult episode, and the characteristics that identify patients who can overcome them better. From September 2019 to August 2020 twenty-three patients followed-up in four Hospital Units of Northeastern of Italy were enrolled. All the patients described an episode linked whit their pathological condition; they mentioned mainly supportive, reactive, or behavioral strategies and an acceptance attitude. The sample characteristics may explain the recurring acceptance attitude; however, the younger individuals, those with a higher level of education and those who faced precedent negative life experiences seem to better overcome challenging events. It can't be taken for granted that patients possess all the skills necessary to overcome the frequent challenging episodes they have to face; for this reason, healthcare professionals should assess their learning and reactive attitude in order to tailor for them therapeutic education paths.